Blood biomarkers to identify patients with different intracranial lesion combinations after traumatic brain injury - Koivikko, Pia; Katila, Ari J.; Takala, Riikka SK.; Hossain, Iftakher; Luoto, Teemu M.; Raj, Rahul; Koivisto, Mari; Tenovuo, Olli; Blennow, Kaj; Hutchinson, Peter; Maanpää, Henna-Riikka; Mohammadian, Mehrbod; et al. (Elsevier BV, 2025)
Introduction
There is a lack of studies examining the most promising blood biomarkers for traumatic brain injury (TBI) in relation to gross pathology types.
Research question
To examine whether the admission levels of blood biomarkers can discriminate patients with different combinations of traumatic intracranial findings from patients with negative computed tomography (CT) scans.
Material and methods
One hundred thirty patients with all severities of TBI were studied. Seventy-five had CT-positive and 55 CT-negative findings. CT-positive patients were divided into three clusters (CL) using the Helsinki CT score: focal lesions (CL1), mixed lesions (CL2) and mixed lesions + intraventricular haemorrhage (CL3). CT scans were obtained upon admission and blood samples taken within 24 h from admission. S100 calcium-binding protein B (S100B), glial fibrillary acidic protein (GFAP), heart fatty-acid binding protein (H-FABP), neurofilament light (NF-L), interleukin-10 (IL-10), total-tau (t-tau), and β-amyloids 1–40 (Aβ40) and 1–42 (Aβ42) were analysed from plasma samples. CT-negative cluster was used as control.
Results
GFAP, Aβ40 and Aβ42 levels differed between the clusters, but not significantly. NF-L and t-tau discriminated CL1 from CT-negative cluster with AUCs of 0.737 and 0.771, respectively. NF-L, t-tau and GFAP discriminated CL2 from CT-negative cluster with AUCs of 0.839, 0.781 and 0.840, respectively. All biomarkers analysed were able to discriminate CL3 and CT-negative cluster.
Discussion and conclusion
All studied biomarkers distinguished the most severely injured cluster, CL3, from CT-negative cluster. The results may reflect the severity of TBI but also show that biomarkers have a variable ability to identify patients with combinations of intracranial traumatic lesions in the examined time window.